2016
DOI: 10.7727/wimj.2016.052
|View full text |Cite
|
Sign up to set email alerts
|

Nephroprotective Effect of the Leaves of Aloe barbadensis (Aloe Vera) against Toxicity Induced by Diclofenac Sodium in Albino Rabbits

Abstract: These results have shown that can normalize oxidative stress and can be used as an effective nephroprotective agent against drug-induced nephrotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…In a study of the effects of AV gel against oxidative stress-induced liver damage, it was determined that AV reduced the formation of lipid peroxidation [28]. Also, when the effects of AV were examined on nephrotoxicity in rabbits, it was determined to have increased the total antioxidant status, reduced the total oxidant status, and increased serum catalase levels due to increased doses of AV [29]. AV has favorable effects on the antioxidant enzyme levels of streptozotocin-induced diabetes in rats.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of the effects of AV gel against oxidative stress-induced liver damage, it was determined that AV reduced the formation of lipid peroxidation [28]. Also, when the effects of AV were examined on nephrotoxicity in rabbits, it was determined to have increased the total antioxidant status, reduced the total oxidant status, and increased serum catalase levels due to increased doses of AV [29]. AV has favorable effects on the antioxidant enzyme levels of streptozotocin-induced diabetes in rats.…”
Section: Discussionmentioning
confidence: 99%
“…It is revealed that it has conspicuous pharmacological activities such as antibacterial (Subramanian et al, 2006;Arunkumar and Muthuselvam, 2009;Saritha et al, 2010;Fani and Kohanteb, 2012;Nejatzadeh-Barandozi, 2013), antifungal (Bajwa et al, 2007;Rosca-Casian et al, 2007;Khaing, 2011;Sitara et al, 2011), antiviral (Zandi et al, 2007), antioxidant (Baradaran et al, 2013;Ray et al, 2013;Kang et al, 2014), cytotoxic (Jose et al, 2014;Shalabi et al, 2015), antidiabetic (Tanaka et al, 2006;Choudhary et al, 2014;Suleyman et al, 2014), anti-inflammatory (Vijayalakshmi et al, 2012;Bhattacharjee et al, 2014), antitumor (El-Shemy et al, 2010;Srihari et al, 2015), nephroprotective (Iftikhar et al, 2015;Virani et al, 2016), antiulcer (Borra et al, 2011) and anti-aging effects which can be used as a moisturizing agent to cure cardiovascular diseases as well as to enhance the immune system (Chatterjee et al, 2013). It is used as an herbal medicine since long time which contains more than 100 bioactive constituents.…”
Section: Issn: 2319-7706 Volume 6 Number 3 (2017) Pp 2152-2162mentioning
confidence: 99%
“…When there is an autoimmune attack against the attachment proteins of keratinocytes, they undergo apoptosis and stimulate several subsequent pathological events. For example, in psoriasis, activated T lymphocytes release various cytokines to stimulate the proliferation of keratinocytes (38). Cytokine-activated keratinocytes can also express a broad array of cytokines, chemokines, and membrane molecules that induce the recruitment and activation of T lymphocytes in the skin (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%